The Enhancement of Cx45 Expression and Function in Renal Interlobar Artery of Spontaneously Hypertensive Rats at Different Age - Li Li (Kidney & Blood Pressure Research, 2015)
Background/Aims: This study was designed to investigate the expression and function of gap junction protein connexin 45 (Cx45) in renal interlobar artery (RIA) of spontaneously hypertensive rats (SHR), and the association between hypertension and enhanced vasoconstrictive response in SHR. Methods: Western blot analysis and pressure myography were used to examine the differences in expression and function of Cx45 in vascular smooth muscle cells (VSMCs) of RIA between SHR and normotensive Wistar-Kyoto (WKY) rats. Results: Our results demonstrated that 1) whole-cell patch clamp measurements showed that the membrane capacitance and conductance of in-situ RIA VSMCs of SHR were significantly greater than those of WKY rats (ppppConclusions: The hypertension-induced elevation of Cx45 may affect communication between VSMCs and coupling between VSMCs and endothelium, which results in an increased vasoconstrictive response in renal artery and might contribute to the development of hypertension.